Pre-service teachers’ competence to teach science through information and communication technologies in South Africa - Jita, Thuthukile (Faculty of Education, University of the Free State, 2016)
Research suggests that there is a need for better training of prospective teachers on information and communication technologies (ICTs) in order to encourage their use for teaching and learning in schools. This paper presents findings on the self-perceptions of competence by pre-service teachers to use ICTs for teaching science content. A mixed method approach was used where 103 final year pre-service teachers completed a questionnaire on their competence to use ICTs for teaching and 21 of them participated in focus group interviews concerning their experiences with ICTs during teaching practice. Results show that pre-service teachers seem to be more competent in the non-technology related skills compared to the technology related knowledge fields and that there are significant variations in their ICT competences. These variations largely result from the uneven opportunities to learn that are provided to the pre-service teachers. More significantly, the directional trend shown by the correlations indicates that the more lecturers or mentor teachers use ICT tools to teach, the more pre-service teachers learn to use ICT tools in their own teaching. The paper concludes with a discussion on the implication of these findings for policy and practice and specifically suggests that there is a need to review the policy guidelines on the development of the teacher education programmes to be more deliberate in their inclusion of ICTs. The key recommended contribution is for teacher preparation programmes at universities to be restructured in order to improve the training of future teachers on the use of ICTs to teach science.
Keywords: Pre-service teachers; Science education; Information and communication technologies; Teaching practice; Teacher education; Technological pedagogical content knowledge (TPACK)